Contaminantes emergentes: productos farmacéuticos en el medio ambiente - Marino, Damián José Gabriel (2012)
The study of emerging pollutants, like pharmaceutical compounds, has become a concern in current environmental research. Pharmaceuticals are used in large quantities and variety. An important fraction after their intake is excreted by persons, via urine and feces, continuously entering into aquatic systems through sewage discharges. Most treatments are inefficient for their complete elimination. The profile of composition and found levels of concentration vary depending on the country and consumption profiles. Lethal effects suggest a low ecotoxicological risk, though when chronic and sublethal effects are taken into account the relevance of this type of pollution becomes of concern. Aquatic organisms are exposed to low concentrations continuously along the life cycle. Associated adverse effects have been detected (e.g.: effects on growth and reproduction, morphological alterations, genotoxicity, among others). Although these type of effects may still not imply an immediate risk to human, some pharmaceuticals are being incorporated into listings of drinking water quality standards. The present study aims to analyze results analysis of pharmaceuticals found in sewage discharges in the country, report prevalence, comparing them with data from other parts of the world. Sewer samples (raw or primary treatment) were collected in the outflow points of discharge of the Río de la Plata estuary and Pampean lakes. Chemical analyses were done by SPE-HPLC/DAD/Ms. The compounds found being more prevalent were: caffeine, ibuprofen, atenolol, carbamazepine and diclofenac. Results encourage the investigation on this type of emergent pollutants, and contribute with relevant information for developments of alternative technologies of water treatment, towards having an adequate quality for the protection of human health and aquatic organisms.